Residuo de Elaeis guineensis (Arecaceae) como absorbente de combustibles para aplicación pasiva en ingeniería contra incendios - Aragón Oconor, Hazel (2024)
Introduction: Spills of flammable liquids can lead to serious accidents, mainly in industrial plants and on roads. To prevent the spread of spills, various forms of collection are used, such as absorption with porous solids. Agroindustrial waste can be used as sorbent materials for flammable liquids. Objective: To determine the sorption capacity of the residual empty-fruit bunch of oil-palm (Elaeis guineensis) and the macaw palm (Acrocomia sp.) nutshell for four organic flammable liquids. Methods: The residual biomasses of E. guineensis and Acrocomia sp. were assessed as sorbents for spilled fuels (diesel, jet fuel, commercial kerosene, and gasoline). Volumetric measurement of liquid-fuel absorption at 24 ºC was taken during a week. Desorption was measured at 50 ºC as the drying kinetics, by using moisture scales. Results: The sorption capacity of the Acrocomia sp. material was not satisfactory, compared to the E. guineensisresidual material, due to differences in the residual architecture of the organic material. This last can absorb 2.4 ± 0.2 cm3 g-1 at 24 ºC, during a one-week period. Diatomite absorbs greater quantities of the organic liquids but, the fluids diffusion at 50 ºC is 0.26 ± 0.09 times more slowly in the mineral matrix, because of the greater pore tortuosity in this mineral matrix. Conclusions: The oil-palm empty fruit bunch of E. guineensis, showed lesser but adequate performance than the sorbing behavior for fire hazard mitigation of diatomite. The nutshell of macaw palm (Acrocomia sp.) did not prove to be useful for this recovery operation.